Die ontmitologiseringsprogram van Rudolf Bultmann - Pelser, G. M. M. (Hervormde teologiese studies, 1987)
Rudolf Bultmann's program of demythologizingAs the heading above indicates, the main purpose of this essay is an endeavour to give an exposition of Bultmann's program of demythologizing. Attention is consecutively given to Bultmann's definition of myth; the problem, according to Bultmann, created for modem man by the mythic worldview of the New Testament and the mythological depiction of the salvation event therein; the impossibility of upholding this view in modem times; the necessity for demythologizing; demythologizing through existential interpretation; results, such as Bultmann's views on speaking about God; the acts of God; God's revelation; the Christ-event and eschatology. The essay is concluded with a short, mainly appreciative evaluation.